2005
DOI: 10.1176/appi.neuropsych.17.1.66
|View full text |Cite
|
Sign up to set email alerts
|

Deficits in Social Knowledge Following Damage to Ventromedial Prefrontal Cortex

Abstract: Patients with damage to the frontal lobes frequently exhibit impaired social behavior, but it is not clear which specific processes are disrupted. The authors investigated the ability to interpret nonverbal emotional expression in patients with lesions involving ventromedial (N=20) or dorsolateral prefrontal cortex (N=9) and in healthy volunteers (N=23). As hypothesized, only patients with ventromedial prefrontal lesions showed impaired task performance relative to normal comparison subjects. These results sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…In the context of a PFC lesion, over-learned heuristics can still be preserved and may become more salient (leading to an increase in professed fundamentalist beliefs), while more diverse, complex and deliberated belief representations become less accessible due to vmPFC damage. In addition, patients withlesions to the vmPFC frequently show impairments in social and reward valuation (Mah, Arnold, & Grafman, 2005; Moretti, Dragone, & di Pellegrino, 2009), and this might lead to changes in their social judgments. For example, patients with vmPFC lesions are more prone to judge extreme (and potentially fundamentalist) behaviors as more acceptable (Cristofori, Viola, et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In the context of a PFC lesion, over-learned heuristics can still be preserved and may become more salient (leading to an increase in professed fundamentalist beliefs), while more diverse, complex and deliberated belief representations become less accessible due to vmPFC damage. In addition, patients withlesions to the vmPFC frequently show impairments in social and reward valuation (Mah, Arnold, & Grafman, 2005; Moretti, Dragone, & di Pellegrino, 2009), and this might lead to changes in their social judgments. For example, patients with vmPFC lesions are more prone to judge extreme (and potentially fundamentalist) behaviors as more acceptable (Cristofori, Viola, et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…While the hippocampus is extensively connected with surrounding MTL structures, including the entorhinal, the perirhinal, and the parahippocampal cortices, we focus here on the connectivity between hippocampus and brain structures that are traditionally thought to be involved in executive function and social interactions, such as the PFC, the amygdala, and the cingulate (Simons and Spiers, 2003; Wood and Grafman, 2003). Both neuropsychological patient and functional neuroimaging studies have demonstrated the involvement of the PFC in complex abilities that require flexible cognition, such as moral reasoning, social conduct, experiencing and recognition of social emotions, assigning affective value to mental representations, and social and emotional decision-making (e.g., Eslinger and Damasio, 1985; Damasio et al, 1990, 1991; Bechara et al, 1994, 1997; Anderson et al, 1999; Greene et al, 2001; Gusnard et al, 2001; Berthoz et al, 2002; Gregory et al, 2002; Shuren and Grafman, 2002; Stuss and Levine, 2002; Bar-On et al, 2003; Beer et al, 2003; Frith and Frith, 2003; Sabbagh, 2004; Mah et al, 2005; Moll et al, 2005; Hynes et al, 2006; D’Argembeau et al, 2008). The hippocampus has extensive connections with the PFC (Simons and Spiers, 2003; Wood and Grafman, 2003), including direct reciprocal connections between the medial PFC and the MTL (Simons and Spiers, 2003), reciprocal connections between the PFC and the perirhinal cortex (Lavenex and Amaral, 2000), unidirectional projections from the hippocampus to the vmPFC (Rosene and Van Hoesen, 1977; Barbas and Blatt, 1995), and bidirectional connections from the subiculum and neocortical medial temporal regions to the vmPFC (Goldman-Rakic et al, 1984; Barbas et al, 1999).…”
Section: The Hippocampus Is Anatomically Connected To Brain Regions Kmentioning
confidence: 99%
“…Thus, the VHIS was vital in establishing improvements in the assessment of those with frontal lobe syndrome. It was found that there may be subgroups of patients with specific social deficits even within groups whose lesion encompasses a larger region, e.g., vmPFC lesions (Sanfey et al, 2003; Goel et al, 2004; Mah et al, 2004, 2005). Administration of the Everyday Problem Solving Inventory (EPSI) suggested that some patients with prefrontal lobe lesions may have impaired social judgment that can be directly revealed only through the use of such relatively novel neuropsychological tests (Dimitrov et al, 1996).…”
Section: Selected Findings From the Vhismentioning
confidence: 99%